Porto alegre: the unfinished victory - Clairmont, Frederic (2003)
The Third World Social Forum at Porto Alegre that ended recently drew even larger numbers of participants than its predecessors. They were people of all ages, of differing propensities drawn together simply by their desire to unite against the threat posed by global capital. Its triumph was due toa confluence of factors - the international justice movement that forms a salient plank of the movement was now conjoined to the large-scale anti-war demonstrations and anti-imperial protests. - Reproduced.
Keywords: Peace